2008
DOI: 10.1111/j.1574-6968.2008.01303.x
|View full text |Cite
|
Sign up to set email alerts
|

Agmatine is essential for the cell growth ofThermococcus kodakaraensis

Abstract: TK0149 (designated as Tk-PdaD) of a hyperthermophilic archaeon, Thermococcus kodakaraensis, was annotated as pyruvoyl-dependent arginine decarboxylase, which catalyzes agmatine formation by the decarboxylation of arginine as the first step of polyamine biosynthesis. In order to investigate its physiological roles, Tk-PdaD was purified as a recombinant form, and its substrate dependency was examined using the candidate compounds arginine, ornithine and lysine. Tk-PdaD, expressed in Escherichia coli, was cleaved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 35 publications
1
34
0
Order By: Relevance
“…Because all archaeal genomes encode a DHS homologue, it can be reasonably assumed that Spd will be required for cell growth in all archaea. It was discovered that Agm is essential for cell growth of Thermococcus kodakaraensis (83) and cannot be substituted by Put or Spd. Subsequently, it was shown that Agm is used to modify a cytidine in the anticodon of archaeal tRNA(Ile) and that the agmatine modification (agmatidine) is essential for decoding AUA (84,85).…”
Section: Polyamines In Archaeamentioning
confidence: 99%
“…Because all archaeal genomes encode a DHS homologue, it can be reasonably assumed that Spd will be required for cell growth in all archaea. It was discovered that Agm is essential for cell growth of Thermococcus kodakaraensis (83) and cannot be substituted by Put or Spd. Subsequently, it was shown that Agm is used to modify a cytidine in the anticodon of archaeal tRNA(Ile) and that the agmatine modification (agmatidine) is essential for decoding AUA (84,85).…”
Section: Polyamines In Archaeamentioning
confidence: 99%
“…Our previous study found that T. kodakarensis PdaD (TK0149) catalyzed the synthesis of agmatine, the first step in polyamine biosynthesis, and was essential for cell growth (32). Agmatine is also a precursor in the synthesis of agmatidine, an agmatine-conjugated cytidine found at the anticodon wobble position of archaeal tRNA Ile (33).…”
mentioning
confidence: 99%
“…5A). A pdaD gene encoding arginine decarboxylase, which catalyzes the synthesis of agmatine, is essential for the growth of T. kodakarensis (32). The plasmid pUD2-⌬bpsA::pdaD was introduced into the strain DAD (⌬pyrF ⌬pdaD).…”
mentioning
confidence: 99%
“…Long-and/or branched-chain polyamines are then produced by the addition of the aminopropyl group derived from decarboxylated S-adenosylmethionine. Previously, we revealed that PdaD Tk catalyzed the first step of polyamine biosynthesis and was essential for cell growth (6). The strain DAD, which lacks the gene pdaD Tk , does not grow in medium without agmatine.…”
Section: (Pathway Ii)mentioning
confidence: 99%
“…A complete genome analysis of T. kodakarensis has been performed, and the pathway of polyamine biosynthesis has been predicted ( Fig. 1) (6,7). It has been speculated that putrescine is synthesized from arginine via agmatine by arginine decarboxylase (PdaD Tk ) and agmatine ureohydrolase.…”
Section: (Pathway Ii)mentioning
confidence: 99%